2020
DOI: 10.5194/egusphere-egu2020-2776
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemistry of Atmospheric Brown Carbon

Abstract: <p>Fundamental understanding of the complex chemistry of light absorbing atmospheric aerosols (aka Brown Carbon - BrC), their physico-chemical properties and environmental impacts is a challenging task because no single method of analytical chemistry is capable of providing the full range of analytical chemistry information. Micro-spectroscopy approaches can visualize individual particles and their internal structures; however, they largely exclude molecular-level information, and are limited to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(66 citation statements)
references
References 210 publications
1
65
0
Order By: Relevance
“…Recent laboratory investigations have shown that photosensitizers can initiate aerosol growth in the presence of gaseous volatile organic compounds, in particular the imidazole derivatives, like imidazole-2 carboxaldehyde, that are formed by reaction of glyoxal with ammonium cations (Rossignol et al 2014). Dark reactions including acid-catalyzed aerosol chemistry of hydronium or ammonium ions, which protonate epoxide and carbonyl groups thus enabling attack by nucleophiles such as water, SO 4 2− , NH 3 and NO 3 − , may be responsible for the ring opening mechanism of epoxides, organosulfate formation by epoxides and carbonyls and C-N-containing lightabsorbing organic species as part of the 'brown carbon' pool (Surratt et al 2010, McNeill 2015, Laskin et al 2015. Night-time chemistry driven by NO 3 radicals also produces organic nitrogen in the aerosol phase that was found to be 5%-12% of OAs during the summer months (Xu et al 2015a).…”
Section: Secondary Sources-multiphase Chemistrymentioning
confidence: 99%
“…Recent laboratory investigations have shown that photosensitizers can initiate aerosol growth in the presence of gaseous volatile organic compounds, in particular the imidazole derivatives, like imidazole-2 carboxaldehyde, that are formed by reaction of glyoxal with ammonium cations (Rossignol et al 2014). Dark reactions including acid-catalyzed aerosol chemistry of hydronium or ammonium ions, which protonate epoxide and carbonyl groups thus enabling attack by nucleophiles such as water, SO 4 2− , NH 3 and NO 3 − , may be responsible for the ring opening mechanism of epoxides, organosulfate formation by epoxides and carbonyls and C-N-containing lightabsorbing organic species as part of the 'brown carbon' pool (Surratt et al 2010, McNeill 2015, Laskin et al 2015. Night-time chemistry driven by NO 3 radicals also produces organic nitrogen in the aerosol phase that was found to be 5%-12% of OAs during the summer months (Xu et al 2015a).…”
Section: Secondary Sources-multiphase Chemistrymentioning
confidence: 99%
“…A: Values of n show no significant dependence on λ, are constrained between 1.5 and 1.7, and are independent of the source depth, MC, and geographic origin. B: κ decreases monotonically with λ between 375 and 532 nm, above which it levels off at κ ≈ 0.002.The current understanding of BrC optical properties has been summarized in previous work, notably byLiu et al (2015) andLaskin et al (2015) [7,29]. Liu et al compared the wavelengthdependent κ values for a variety of atmospheric light absorbing organic material such as m-xylene and toluene oxidation products…”
mentioning
confidence: 99%
“…Our findings underscore that OD s is a better optical depth measure than OD c for applying appropriate correction factors when estimating particle-phase light absorption from filter-based techniques. combustion phase and can range ∼ 0.01-1 m 2 g −1 at 550 nm (Laskin et al, 2015).…”
mentioning
confidence: 99%